Coleochaete Breb. and Bulbochaete Agardh from North-Eastern Uttar Pradesh, India - Srivastava, A. K.; Mishra, P. K. (Ecoprint: An International Journal of Ecology, 2010)
Present communication deals with morpho-taxonomic descriptions of four taxa that includes two genera and four species of class Chlorophyceae. These species are Coleochaete scutata Brebisson Coleochaete soluta (Brebisson) Pringsheim, Bulbochaete nordestedtii (Wittrock) Him and Bulbochaete pseudoaerolata Bock and Bock. One of the species B. pseudoaerolata Bock and Bock is a new record for India. Key words: Fresh water, Chlorophyceae DOI: 10.3126/eco.v16i0.3474 ECOPRINT 16: 59-63, 2009